Pengaruh Social Media Marketing dan Product Review Terhadap Purchase Decision Parfum Lokal dengan Trust Sebagai Moderasi - Felisha Aulia Aulia; Andi Hidayat Muhmin (MES Bogor, 2026)
The perfume industry in Indonesia is experiencing rapid growth, which has led to increased competition between local brands and encouraged companies to improve their marketing strategies to be more efficient. This study aims to investigate the influence of social media marketing and product reviews on the purchase decision of HMNS local perfume products, as well as to examine the role of trust as a moderating variable in the relationship between social media marketing and purchase decision. The research population consists of active social media users residing in Greater Jakarta and aged 18-34 years. The sample consisted of 141 respondents selected using a non-probability method with purposive sampling technique. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of this study indicate that social media marketing and product reviews influence purchase decisions, both separately and simultaneously. However, this study found that trust does not moderate the relationship between social media marketing and purchase decisions. These findings indicate that consumers' purchase decisions for local perfumes are more influenced by social media marketing and information from product reviews than by trust factors. This study has limitations in terms of the area researched, so it is recommended that future studies expand the scope of the region and add other variables such as brand image, perceived value, and brand awareness to gain a more comprehensive understanding.